KONFLIK ANTAR KELAS MASYARAKAT BUTON DESA SAMPUABALO DAN DESA GUNUNG JAYA KECAMATAN SIOTAPINA KABUPATEN BUTON - ARUPALAKA, LA ODE; DIRMAN, LA ODE; Aso, La (Jurnal Penelitian Budaya, 2021)
The objective of this study is to describe the causes of conflict intra society classes of Butonese, Sampuabalo Village and Gunung Jaya Village, Siotapina District of Buton Regency by using a qualitative descriptive approach to describe what are the backgound of the conflict problem. In analyzing the theoretical data it was used the Functional Theory of Coser and Pieree Felix Bourdieu's Social Interaction about Habitus, Capital and Domain to analyze the root causes of class conflict in the Buton community, Sampuabalo Village and Gunung Jaya Village, Siotapina District of Buton Regency. This research uses a qualitative approach. There are two types of data used in this study, namely primary data and secondary data. Collecting data in this study were done by using observation technique, interviews technique, and document study. Based on the results of data analysis, the results of this study showed Â that: The backgroundof the problem of conflict intra society classes of the Butonese, Sampuabalo Village and Gunung Jaya Village, Siotapina District of Buton Regency were caused by several factors, namely: (1) the history of the two villages with different social classes (aristocrat and non-aristocracy, (2) ongoing individual and group conflicts, (3) educational factors, (4) identity factors, (5) incomplete conflict handling, (6) latent conflicts, (7) dysfunction of traditional institutions in society. , and (8) lack of employment.Keywords: conflict, class of society, Buton Regency